40 years of PCE superplasticizers - History, current state-of-the-art and an outlook. (July 2022) - Lei, Lei; Hirata, Tsuyoshi; Plank, Johann
Abstract: 2021 marks the 40 th year since polycarboxylate superplasticizers (PCEs) have been invented by Nippon Shokubai company in Japan. This invention clearly represents a major breakthrough and milestone in modern concrete technology. In this review article, at first Dr. Hirata – the main inventor of PCE superplasticizers – reports on the history behind their invention and market entry. Thereafter, recent developments and innovations in PCE technology are presented. As of today, the market offers a wide range of chemically different PCE products, among them HPEG and IPEG PCEs have occupied the largest market share because of their superior cost-effectiveness. At this moment, novel types of PCEs including EPEG and GPEG PCEs are being introduced, thus enriching the family of vinyl ether (VPEG) superplasticizers. In spite of the huge success of PCEs, also challenges in specific applications such as their sensitivity towards clay contaminants or the viscous ("sticky") flow behavior of concrete mixed at low w/c ratios became obvious and will be addressed. Furthermore, as the concrete industry currently undergoes a fundamental transition to low-carbon binders in order to reduce anthropogenic CO2 emission, PCE superplasticizers suitable for such low or zero clinker binders including calcined clay blended cements or alkali activated slags are being sought and the current state-of-the-art in this field will be discussed. Finally, the future perspectives of PCE technology in a dramatically changing industry are assessed and the pivotal role of PCEs in this mega transition faced by the construction industry will be pointed out.